2018
DOI: 10.1101/351437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of correlated complexity in the radically different courtship signals of birds-of-paradise

Abstract: Ornaments used in courtship often vary wildly among species, reflecting the evolutionary interplay between mate preference functions and the constraints imposed by natural selection. Consequently, understanding the evolutionary dynamics responsible for ornament diversification has been a longstanding challenge in evolutionary biology. However, comparing radically different ornaments across species, as well as different classes of ornaments within species, is a profound challenge to understanding diversificatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 106 publications
(76 reference statements)
0
29
0
Order By: Relevance
“…This study provides an emblematic example of the power of sensory drive in predicting the direction of evolution of otherwise highly unpredictable sexual traits. Also, by revisiting a pattern predicted for decades, but never tested before – that ‘high‐flying […] displays are most characteristic of birds of the open country' (Armstrong, , p. 257) – we offer a contribution to the ongoing efforts to disentangle the evolutionary drivers of complex avian gestural displays (Ligon et al, ; Miles et al, ; Miles & Fuxjager, , ; Soma & Garamszegi, ). Such efforts had shown that biogeographical, phenotypic, environmental and life‐history factors all influence sexual display evolution in passerines at the family level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study provides an emblematic example of the power of sensory drive in predicting the direction of evolution of otherwise highly unpredictable sexual traits. Also, by revisiting a pattern predicted for decades, but never tested before – that ‘high‐flying […] displays are most characteristic of birds of the open country' (Armstrong, , p. 257) – we offer a contribution to the ongoing efforts to disentangle the evolutionary drivers of complex avian gestural displays (Ligon et al, ; Miles et al, ; Miles & Fuxjager, , ; Soma & Garamszegi, ). Such efforts had shown that biogeographical, phenotypic, environmental and life‐history factors all influence sexual display evolution in passerines at the family level.…”
Section: Discussionmentioning
confidence: 99%
“…While these case studies belong in the sensory drive realm (Cummings & Endler, ) and may be indicative of an evolutionary link between habitat and display, a phylogenetic comparative approach is the most appropriate way to uncover such a link (Harvey & Pagel, ). Phylogenetic comparative evidence accumulated to date suggests that (micro)habitat may influence aspects of avian and saurian displays such as repertoire size (Ligon et al, ; Miles & Fuxjager, ; Ord, Blumstein, & Evans, ) and repetition pattern (Ord & Martins, ; but see Perez et al, ). However, the role of habitat as a force that determines which elements of display repertoires should evolve – rather than how many elements – has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The utilization of forest openings are well studied in avian biology, where males often construct and clear elaborate arenas to perform intricate visual displays for females (i.e. the genus Parotia or six-plumed birds of paradise) [38]. However, to our knowledge, the visual capabilities across vertebrate animal species has never been compared to examine evolutionary investments in the nervous system that correlate with visual courtship.…”
Section: Discussionmentioning
confidence: 99%